Comparison focus in intergroup comparisons: Who we compare to whom influences who we see as powerful and agentic. - Bruckmüller, Susanne; Abele, Andrea E. (Personality and social psychology bulletin, 2010)
In intergroup comparisons one group usually becomes the implicit norm that other groups are compared to. Three studies address the consequences that the direction of the comparison has for perceptions of the compared groups. For real groups (Experiment 1) and fictitious groups (Experiments 2 and 3) participants perceived a group as more powerful and higher in status when it had been the norm rather than the effect to be explained in a text comparing two groups. Moreover, norm groups and their "typical" members were perceived as more agentic and less communal than comparison groups, and these attributions were mediated by the ascription of power. The authors conclude that systematic ways of explaining one group rather than another could serve as a subtle tool to perpetuate the status quo of intergroup power relations. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: intergroup comparisons; social comparison